Rodent Models of Optic Neuritis - Redler, Yael; Levy, Michael (Frontiers in Neurology, 2020)
Optic neuritis (ON) is an inflammatory attack of the optic nerve that leads to visual disability. It is the most common optic neuropathy affecting healthy young adults, most commonly women aged 20-45 years. It can be idiopathic and monophasic, or as part of a neurologic disease such as multiple sclerosis with recurrence and cumulative damage. Currently, there is no therapy to repair the damage from optic neuritis. Animal models are an essential tool for the understanding of the pathogenesis of optic neuritis and for the development of potential treatment strategies. Experimental autoimmune encephalomyelitis (EAE) is the most commonly used experimental rodent model for human autoimmune inflammatory demyelinating diseases of the central nervous system (CNS). In this review, we discuss the latest rodent models regarding optic neuritis, focusing on its recent achievements and developments.